The Power of Utterances in Indonesian President Candidates First Debate: A Pragmatic Study of Conversational Implicature - Hastuti, Nuri Puji; Rohmadi, Muhammad (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2024)
Utterances in the political field can be powerful things to communicate, influence regulation, or make big mass mobility. However, people have a lack of capability to interpret the meaning. It creates problems such as false understanding, apathy, and division. Based on the problems, the aim of the research is to describe and explain the conversational implicature utterances in the biggest democratic party in Indonesia, the president candidate's first debate. A descriptive qualitative method has been used consisting of data collection, data reduction, data display, and conclusion. The data were collected by taping- taking notes with purposive sampling. The validities were checked by theories, resources, and methods triangulations. Based on the result, the conversational implicatures consist of 1) description of president candidates background and their vision and mission that relate to the debate topic, 2) request to citizens to have critical thinking of political problems, 3) critique to decrease the electability of other president candidates by describing their failures or violation, 4) clarification for the allegation from other president candidates, 5) persuasion to citizens to vote the speaker by showing achievement and dedication. The conversational implicatures have been conveyed well. The first implicature becomes the most dominant data. This means, in a conversational implicature perspective, the speakers mostly use utterances as media to describe their vision and mission which consists of making regulations and solving problems in law, human rights, anticorruption, democracy, strengthening, public service improvement, and community as the representation of political power. Keywords: power, utterances, Indonesian president candidates first debate, pragmatic, conversational implicature.